A Study on Hearing Impairment in Type 2 Diabetes Patients in Comparison to Normal Using Pure Tone Audiometry - Malathi Nagini Priyanka Javaji, Dr.JM Harsoda (South Eastern European Journal of Public Health, 2025)
Introduction: Pure-tone audiometry is a psychoacoustic test based on hearing thresholds, frequency-modulated sound. Both air and bone conduction thresholds are tested with PTA. this is a case-control study to determine hearing loss with T2DM and those without T2DM about age, BMI, and duration of diabetes using PTA Aim and Objectives: To study the effect of type 2 diabetes on auditory structures through PTA in comparison with controls Materials and Methods: Patients with type 2 diabetes with hearing impairment, both gender was included with an age limit between 30-60 years; minimum duration of diabetes after the diagnosis was 7 years and also 30 normal subjects as controls. Results: There is no statistically significant relation regarding age distribution in between the groups(P-value>0.05). There is no statistically significant relation regarding sex distribution in between the groups(P-value>0.05). There is a statistically significant relation regarding blood glucose levels between the groups(P-value<0.05). There is a highly significant relation between PTA of control group and T2DM group indicating that the altered blood sugar levels have an impact on auditory threshold.